Interactions between vaginal local cytokine IL-2 and high-risk human papillomavirus infection with cervical intraepithelial neoplasia in a Chinese population-based study - Zhu, Ruoxi; Wang, Wenhao; Yang, Aiming; Zhao, Weihong; Wang, Wei; Wang, Zhilian; Wang, Jintao; Hou, Yongli; Su, Xiaoqiang; Zhang, Lili; Feng, Bo; Yang, Jing; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Although interleukin-2 (IL-2) has long been associated with cancer development, its roles in the development of cervical cancer remains unclear. Few studies examined the associations between IL-2 and high-risk human papillomavirus (HPV) with risk of cervical intraepithelial neoplasia (CIN). Objective: We aimed to assess the association of IL-2 and high-risk HPV infection with risk of CIN as well as their interactions on the risk of CIN. Design: We performed a cross-sectional analysis of screening data in 2285 women aged 19-65 years who participated in an ongoing community-based cohort of 40,000 women in Shanxi, China in 2014-2015. Both categorical and spline analyses were used to evaluation the association between IL-2 in the local vaginal fluids and prevalence of CIN. In addition, 1503 controls were followed up until January 31, 2019), the nested case-control study design was adopted to evaluate the association of vaginal lavage IL-2 levels and the risk of CIN progression. Results: After adjusting for potential confounders, IL-2 levels were statistically inversely associated with prevalence of CIN (the 1st versus 4th quartile IL-2 levels: the respective odds ratio [OR] and 95% confidence intervals [CI] was: = 1.75 [1.37, 2.23] for CIN, 1.32 [1.01, 1.73] for CIN I, and 3.53 [2.26, 5.52] for CIN II/III). Increased IL-2 levels were inversely associated with prevalence of CIN (P-overall<0.01, P-nonlinearity<0.01 for CIN; P-overall<0.01, P-nonlinearity = 0.01 for CIN I; P-overall <0.01, P-nonlinearity = 0.62 for CIN II/III). The highest prevalence of CIN was observed in women with high-risk HPV, who also had the lowest IL-2 levels (P-interaction < 0.01). Nested case-control study observed an inverse association between IL-2 levels and risk of CIN progression (OR=3.43, [1.17, 10.03]). Conclusions: IL-2 levels in the local vaginal fluids were inversely associated with the risk of CIN in Chinese women either with or without high-risk HPV infection.